Application Of Qiraati Method to Improve Reading Ability Al-Qur'an - Aswan, Rani; Amin, Muh.Agil; Hendri, Hendri (Educational Journal of Learning Technology, 2024)
The ability to read the Qur'an is an important skill for junior high school students, but there are still many obstacles to achieving it. This study aims to measure the effectiveness of the Qiroati method in improving the ability to read the Qur'an in class VIII A students at State Junior High School 3 Palopo. This classroom action research uses the Kemmis and McTaggart model with four stages: planning, implementation, observation, and reflection. The instruments used are interviews, observation, and documentation. The results show that the Qiroati method significantly improves the ability to read the Qur'an, especially in pronouncing the hijaiyah letters correctly. In the second cycle (post-test), the success rate reached 90.30% with an average score of 80.2%. In conclusion, the Qiroati method is effective and practical in learning to read the Qur'an and is recommended for use in similar situations.